Pengembangan Buku Komik Cerita Rakyat untuk Pembelajaran Bahasa Indonesia Materi Gagasan Pokok Kelas IV - Rizka Devi Nur Safitri; Arya Setya Nugroho; Ismail Marzuki (STIKes Ibnu Sina Ajibarang, 2025)
This research aims to describe the process of developing folklore comic books for learning Indonesian, main idea material for class IV. Type of R&D (Research and Development) development research using the 4D model (Define, Design, Develop, and Disseminate). This research was conducted at MI Al-Huda Banyutami in the even semester. The subjects of this research were 9 grade 4 students. Data collection techniques used validation questionnaires from material experts, language experts, graphics experts, and student response questionnaires. The research results on comic book development used a 4D model, but in this research, only 3 stages were used (Define, Design, and Develop). The results of the validity of folklore comic books can be seen from the validation results of the expert team, namely material experts who got a score of 91.6% which was categorized as very valid, language experts with a score of 93.75% in the very valid category, and graphics experts who got a score of 90.9% in the very valid category and student questionnaire responses which got a percentage of 93% in the very good category.